ANALISIS STRUKTUR TOPIK KOMEN KALIMAT DALAM NOVEL SURAT WASIAT KARYA SAMSOEDI - Ramdani, Ikhsan; Triwahyuni, Heti (Universitas Batanghari, 2025)
This study aims to describe the structure of topics-comments and syntactic functions in the novel Surat Wasiat by Samsoedi. The background of this research is based on the importance of understanding sentence structure in literary works as an effort to preserve language and improve syntactic learning. The research method used is qualitative descriptive with a discourse analysis approach. The research data totaled 155 sentences containing a topic-comment structure, analyzed based on the categories of words and phrases that occupied the topic, as well as the pattern of their syntactic functions. The results showed that the fillers of the topic included nouns, pronouns, question words, dead nouns, nominal phrases, numeral phrases, verbal phrases, prepositional phrases, and tense phrases. Declarative sentences dominate with a total of 148 sentences, while interrogative sentences amount to 7 sentences. Topic syntactic functions are found in subjects, predicates, and descriptions with variations in patterns such as (J–C), (J–C–K), and (J–C–Pang), which play the role of actors, receivers, tools, outcomes, places, or time. This study confirms that the diversity of topic-comment structures contributes to the richness of the meaning of the novel's discourse